High Power and Long-distance Power Transmission System in Deep Sea Mining - ZHU Jianbo; HE Duochang; ZHANG Dinghua (Kongzhi Yu Xinxi Jishu)
With the depth of seabed mining increasing, required power of deep sea equipment is increasing, its motor power can even be several megawatts. Compared with land power grid, the capacity of ship power grid is small, direct start of high-power motor will cause serious impact on ship power grid, so soft starter is needed to reduce starting current. Some previous projects used thyristor soft start device to start motor, but there are problems such as the inability to start motor, voltage resonance, and umbilical insulation breakdown. In order to realize motor start-up impact-free and real-time control, this paper matches and calculates the parameters of the transformer and the power supply umbilical cable according to the start-up characteristics of the underwater motor and the parameters of the stator and rotor, and proposes a high power long-distance deep sea power transmission system, which has functions of online monitoring and grounding detection, and can meet the requirements of power transmission, distribution and control in water depth of 2 000 m, and built a simulation model for system simulation to realize the smooth start and real-time regulation of underwater high power motors. Correctness of the power transmission system parameter calculation and the feasibility of scheme are proved through the sea trial, which provides a reference for subsequent larger-scale research and commercial projects.